Endocavity Ultrasound Transducers: Why High-Level Disinfection Is Necessary - Westerway, Susan Campbell; Basseal, Jocelyne M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
As a medical imaging modality, ultrasound is used by a wide cross-section of practitioners including radiologists, obstetricians, gynecologists, gastroenterologists, urologists and cardiologists. The increasing popularity of ultrasound as a diagnostic tool is due not only to the ease of use and portability of systems, but also to the perceived safety aspect of the examination. This latter point needs to be examined. As with any reusable medical device, the ultrasound transducer, also known as a probe, could potentially be a vector for the transmission of pathogenic viruses and fungi between patients if not correctly disinfected after each use. This transmission risk is magnified for an endocavity transducer that has come in contact with the vagina, anal canal or oral cavity, as it could be contaminated with organisms transmitted by blood or mucosal, genital or rectal secretions. Based on the Spaulding system, transducers that come in contact with mucous membranes are classified as semi-critical devices that require high-level disinfection (HLD) after each patient procedure. This HLD process should eliminate all microorganisms except high numbers of bacterial endospores. Only a small number of countries worldwide have implemented transducer reprocessing guidelines that adhere to the Spaulding classification and recommend HLD for endocavity transducers. Overall, there is a lack of conformity among global health agencies regarding the use of HLD for endocavity transducers. This is primarily due to the perception that the infection transmission risk is negligible and that if an endocavity transducer has been covered with a single-use sheath for the procedure, then low-level disinfection provides sufficient protection against pathogen transmission. The objective of this study was to review the published risk of infection transmission from endocavity transducers. By highlighting the outbreaks and case reports that implicate pathogen transmission from transducers, we posit that HLD should be a global standard of practice for the reprocessing of endocavity transducers. It requires substantial time for national health administrations to develop and legislate new recommendations, and for practice changes to be accepted and implemented by healthcare providers. We recommend that Joint Commission International (JCI) and other equivalent organizations enforce the use of HLD of endocavity ultrasound transducers during their accreditation reviews.
Keywords: ultrasound; infection control; transducers/probes; reprocessing